Classification of clinical risk in people with AIDS followed up in specialized care - Oriana Deyze Correia Paiva Leadebal; Leidyanny Barbosa de Medeiros; João Agnaldo do Nascimento; Aline Aparecida Monroe; Jordana de Almeida Nogueira
ABSTRACT Aim: To develop a clinical risk stratification score for people living with AIDS and to analyze its association with clinical and sociodemographic aspects. Method: Cross-sectional study involving 150 adults with AIDS, in outpatient follow-up. A structured instrument was applied and, sequentially, inferential statistical techniques on the developed score. Results: 45.3% of the participants were classified as in high clinical risk. TL-CD4+ <500cel/mm3 count, detectable viral load, presence of opportunistic diseases, chronic diseases and clinical manifestations were associated with high clinical risk. There was a significant difference in the mean risk between the categories of variables employment status (p = 0.003) and economic class (p = 0.035). There was a higher risk for brown people (OR = 5.55), unemployed status (OR = 16,51) and belonging to classes C (OR = 20.07) and D (OR = 53,32), and a lower risk for individuals with higher schooling (OR = 0.02). Conclusion: The proposed score quantifies clinical situations and points out sociodemographic aspects that predispose to instability and aggravation of AIDS, supporting the qualification of care.